Frostbite Injury and Disability - Biçer, Ümit; Çolak, Başar; Doğan, Türker; Tekinalp, Haldun; Akansel, Gür (The Bulletin of Legal Medicine, 2002)
Dispute regarding ailment resulting from occupational injury is occasionally brought to the courtroom with subsequent request of forensic medicine expert opinion. The case reported has a history of prolonged exposure to severe cold weather on duty in 1987. He developed symptoms of frostbite and sought care at several nonacademic medical facilities. The medical records from these institutions reflect the diagnoses “Buerger’s disease” and “Buerger’s disease, status post sympathectomy”. He was then referred to an academic institution where “no evidence for peripheral arterial insufficiency in the lower extremities that could result from frostbite injury” was found. He was granted disability in 1997 due to the injury in his feet, with the diagnosis of Buerger’s disease. However, the Retirement Fund, pointing at the conflict between medical records from different institutions, questioned his status of retiree from work-related injury and declined his request for retirement pay until clarification of the matter. The patient went to court with the claim that the injury in his feet resulted from frostbite and not Buerger’s disease. The court requested expert opinion from the department of forensic medicine (Kocaeli University School of Medicine) in 2001. Upon initial evaluation, a contradiction was noted between the patient history and the pathological findings. A decision was made to further evaluate the current vascular status of the patient’s lower extremity. Digital subtraction angiography and color Doppler ultrasonography documented the lack of permanent vascular injury that could result from Buerger’s disease. According to these findings, it was concluded that the present injury was unlikely to have been caused by Buerger’s disease but highly likely to result from microvascular disease due to cold exposure. Based on this report, the court concluded that the patient had experienced an occupational injury and could legally claim the rights of early retirement. Key Words: Disability, Buerger’s disease, Frostbite injury, Forensic medicine